Controle de constitucionalidade no processo administrativo: corolário do devido processo legal - Cabral, Thales Francisco Amaral (2015)
The dissertation analyses the judicial review of legislation in Public Administration, questioning the possibility of such competence in the course of administrative process on the basis of the due process clause. After studying the logical-legal aspects of the constitutionality of legislation phenomenon, the constitutionality control instruments in the Brazilian legal system is examined. A broad definition process that could include administrative processuality is adopted. It is argued that the clause of due process functions as procedural validity requirement, limiting thus the content of the decisions and the form to decide. In the last chapter, the hypothesis of due process, the procedural validity requirement condition, support the constitutionality control laws in the administrative process is verified.